Avaliação da função tireoidiana e polimorfismo THR92ALA-D2 do gene da desiodase tipo 2 como biomarcadores de mortalidade na Covid-19 - Beltrão, Fabyan Esberard de Lima (2021)
The new coronavirus (SARS-CoV-2) can cause pulmonary and systemic inflammation and multiple organ dysfunction. Findings suggest that dysfunctions in in-hospital thyroid hormones and the Non-Thyroid Disease Syndrome (NTIS) are associated with poor clinical outcomes during COVID-19 hospitalization. Moreover, researchers found correlations between type 2 deiodinase (especially his Thr92Ala-DIO2 polymorphism) and acute lung injury and pulmonary fibrosis. However, studies that assess thyroid function and THR92ALA-D2 polymorphism in patients with COVID-19 are still insufficient and inconclusive. This study aimed to evaluate the association of thyroid function biomarkers, NTIS prevalence, and Thr92Ala polymorphism-DIO2 with COVID-19 mortality and COVID-19 severity biomarkers in the hospital setting. This study is a cohort, observational, longitudinal and prospective study that evaluate COVID-19 hospitalized patients. Our study includes a total of 274 patients with COVID-19 admitted to the Metropolitan Hospital of the João Pessoa-PB city (Northeast of Brazil) between June and August 2020. We assess the patient's thyroid hormones (TSH, free T3, free T4, and reverse T3), COVID-19 biomarkers, and Thr92Ala-DIO2 polymorphism genotype. Results: The cut-off level of free T3 (≤2.6 pg/mL) and reverse T3 (≤0.38 ng/mL) were associated with 3.46 and 5.94 OR of mortality, respectively. NTIS (fT3 ≤ 2.0 pg/mL) was correlated with 7.05 OR of mortality ([CI 1.78– 28.3], p = 0.005). The cut-off product level of rT3xfT3 (≤ 1.29) was associated with 8.08 OR mortality ([CI 3.14–24.2], p = 0.0001). We assessed 220 patients (we lack data of 54 patients) Thr92Ala-DIO2 polymorphism genotype and found the following result: Thr/Thr (n=79), Ala/Thr (n=119) and Ala/Ala (n=23). The overall mortality was 17.3% (n=220), lethality was lower in Ala/Thr patients (12.6%) when compared to Thr/Thr patients (21.7%) or Ala/Ala patients (23%). The Kaplan-Meier curve showed a significantly higher chance of survival in patients with the heterozygous allele (Ala/Thr) than patients with homozygous alleles (HR 0.53, p = 0.048). Univariate and multivariate logistic regression adjusted for multiple covariates showed a mortality Ala/Thr reduction that ranged from 51-66%. To assure our results, we did a meta-analysis of 5 studies (including this one) about Thr92Ala-DIO2 polymorphism that confirmed the association of the Ala/Thr genotype with better clinical outcomes.